Envenomation by a western green mamba (Dendroaspis viridis) – A report of three episodes in Switzerland. (October 2019) - Fuchs, Joan; Weiler, Stefan; Meier, Jürg
Abstract: The African elapid snake genus Dendroaspis comprises four species, with D. polylepsis the most dangerous of them. D. viridis is believed to cause stronger neurotoxic symptoms than the potentially least toxic of the genus, D. angusticeps, but seems less toxic compared to either of the D. jamesoni species ( D. j. jamesoni (TRAILL 1843) and D. j. kaimosae (Loveridge 1936)). We present three episodes of bites by D. viridis in the same patient, sustained on three different occasions, caused by three different and unrelated snakes. While the first bite remained oligosymptomatic with a slight tightness of the throat and speedy resolution of symptoms without specific therapy, episodes two and three resulted in the patient developing massive local swelling. However, the patient showed only minimal neurologic and systemic symptoms such as tightness of the throat and a tingling sensation of the body. Episode two resolved with fasciotomy after compartment syndrome was diagnosed with a measured intracompartmental pressure of 52 mmHg. In episode three, antivenom was administered with good resolution of symptoms. The clinical courses in this patient were remarkable as he displayed mainly local symptoms after three individual bites by a supposedly neurotoxic snake. Highlights: Describes three episodes of human envenomation by the Western green Mamba Dendroaspis viridis . The patient developed only minimal neurologic, but severe local symptoms. Related species like D . polylepsis can cause potentially fatal neurotoxicity. The patient recovered with fasciotomy and antivenom.